ANALYSIS OF THE POPULARITY OF THE USE OF STANDARD INDONESIAN AND SLANG LANGUAGE AMONG TEENAGERS IN YOGYAKARTA - Asyifa Luthfiana Arfani; Aninditya Sri Nugraheni (Sunan Kalijaga International Journal on Islamic Educational Research, 2020)
Language has a vital role in this aspect of life. Language is a communication tool to convey ideas, ideas, and also one's desires to others. In its development, language has been influenced by several things, including the users of the language itself. At present, the Indonesian language has experienced various significant changes from year to year. Teenagers have a considerable influence on the development of language in a region because they are the main focus of the outside world in measuring the ability of a nation. Various problems began to emerge regarding the Indonesian language problem, which is currently starting to erode and replaced with slang. The purpose of this writing is none other than to know the extent of the development of the Indonesian language and to maintain the position of Indonesian, especially among teenagers today. An apparent influence on teenagers now is their obsession with the use of slang which they believe can make them look cooler and more contemporary. Some adolescents also claimed that they started to be ordinary with the current position of Indonesian. The pride that began to fade in the souls of adolescents must begin to be reinvested given how influential the role of adolescents in facing competition in the industry 4.0 today.